2013
DOI: 10.1016/j.pain.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias to pain-related information: A meta-analysis

Abstract: This meta-analysis investigated whether attentional bias, i.e. the preferential allocation of attention to information that is related to pain, is a ubiquitous phenomenon. We also investigated whether attentional bias effects are related to the methodological quality of the study, to procedural differences in their measurement, or to individual differences in pain severity, pain-related fear, anxiety and depression. Results indicated that individuals who experience chronic pain (n=1023) display an attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
359
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 287 publications
(403 citation statements)
references
References 154 publications
(154 reference statements)
40
359
4
Order By: Relevance
“…Pain captures attention and urges the person to suspend the ongoing activity and engage in protective actions [14]. The degree to which pain or signals of impending pain capture attention and are evaluated as requiring immediate action is influenced by various factors [11,37]. For example, pursuing a highly valued goal has been found to lower the attentional demand of pain [30].…”
Section: Interruption Cuementioning
confidence: 99%
“…Pain captures attention and urges the person to suspend the ongoing activity and engage in protective actions [14]. The degree to which pain or signals of impending pain capture attention and are evaluated as requiring immediate action is influenced by various factors [11,37]. For example, pursuing a highly valued goal has been found to lower the attentional demand of pain [30].…”
Section: Interruption Cuementioning
confidence: 99%
“…Recent meta-analyses of such studies showed that attentional bias was overall smaller in magnitude than would have been expected, and that its manifestation was dependent upon specific procedural aspects, such as type of stimuli and presentation time of stimuli (Crombez, Van Ryckeghem, Eccleston, & Van Damme, 2013;Schoth, Nunes, & Liossi, 2012). One potential explanation for these underwhelming results is that visual representations of pain may not sufficiently capture bodily threat, and that the adaptive value of bias to (the location of) such stimuli is very limited Van Damme et al, 2010).…”
mentioning
confidence: 99%
“…According to the vigilance-avoidance hypothesis AB towards pain-related information may be found early in time (≤500ms), but may reverse and become attentional avoidance later on (>500ms) [11,12]. As yet, there is no evidence for this idea [5,15].Research on attentional bias has substantially increased during the last years. In doing so, most researchers have adapted experimental paradigms and models of attentional bias from experimental psychopathology.…”
mentioning
confidence: 99%
“…Also patients with chronic pain display an AB towards pain-related information, although it is not as robust as is often assumed [5,15]. Despite extant research several challenges remain, and, there is a strong need for systematic investigations in large samples [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation